Bioremediation, Biosorption, and Biodegradation of the Textile Dye Reactive Black 5 by Life Cultures of Trichoderma asperellum LBKURCC1 - Titania Tjandrawati Nugroho; Putri Nabilah; Nuria Wulandari; Yuana Nuralita; Andi Dahliaty; Yanti Yanti (Jurnal Natur Indonesia, 2023)
Reactive black 5 (RB5) is an azo dye widely used in the textile industry for dyeing fabrics. It is categorized as a recalcitrant dye that is hard to degrade and an environmental pollutant. Therefore, textile waste effluents containing this dye must be treated to remove or degrade the dye, before being released into the environment. One method that can be used to degrade synthetic dyes such as RB5 is to use biological methods, by directly using live fungal cells or using laccase enzymes. Trichoderma asperellum LBKURCC1 is a filamentous fungus isolated from cacao plantation soil in Riau, Indonesia, and it is a laccase enzyme producer. To be able to determine the ability of T.asperellum LBKURCC1 life cultures to decolorize RB5 dye, several RB5 dye removal tests were carried out. Incubation of 50 ppm RB5 with life cultures of T. asperellum LBKURCC1 at room temperature (30°C, pH 6.5) for 24 hours resulted in 22% bioremediation, 3.2% biosorption and 19.1% biodegradation of the RB5 dye. The results of this study show that the live culture of T.asperellum LBKURCC1 is capable of biodegrading RB5. This is indicated by the degradation of RB5 by extracellular enzymes produced by these filamentous fungi.